2019
DOI: 10.15218/ejnm.2019.19
|View full text |Cite
|
Sign up to set email alerts
|

Coping Strategies among Caregivers of Children with Acute Leukemia at Nanakali Hospital in Erbil City

Abstract: Childhood cancer is an increasing and prevalent type of chronic disease worldwide. Leukemia represents 25% of all cancers in children under the age of 15 years and is the most common type of cancer in this age group [1]. Acute leukemia is the most common malignancy that affects children. In 2018, leukemia accounted for 6.6% of 25,320 new cases of cancers in the Iraqi population [2]. In Erbil, during 2016-2018, there were more than 120 cases of children with leukemia registered at the Nanakali Hospital for Bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
0
0
Order By: Relevance
“…Forty percent of the studied children were diagnosed with leukemia. These results were in accordance with a study done by Hamad and Shaker [17] , who found that more than half (52%) of the children were females, and the majority (88.9%) of them were diagnosed with leukemia. On the same perspective, Motlagh et al [24] found that the mean age of children with cancer was 5.57 years, 47.1% of the children were female, and 52.9% were male.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Forty percent of the studied children were diagnosed with leukemia. These results were in accordance with a study done by Hamad and Shaker [17] , who found that more than half (52%) of the children were females, and the majority (88.9%) of them were diagnosed with leukemia. On the same perspective, Motlagh et al [24] found that the mean age of children with cancer was 5.57 years, 47.1% of the children were female, and 52.9% were male.…”
Section: Discussionsupporting
confidence: 92%
“…All of the caregivers who participated in the current study were mothers. These results supported by a study done by Hamad and Shaker [17] to assess the coping strategies among 54 caregivers of children with acute leukemia in Iraq. The study results proved that caregivers' mean age was 36.53± 7.53 years, and the majority of chief caregivers (87%) were mothers.…”
Section: Discussionsupporting
confidence: 77%